Heterogeneous provincial prices and monetary policy in South Africa: A wavelet-based quantile regression analysis - Abdul-Aziz Iddrisu; Imhotep Paul Alagidede (Central Bank Review (CBR), 2021)
Although economic agents in different parts of a country face heterogeneous prices, empirical literature continue to assume homogeneity in the monetary policy-inflation nexus, with dire consequences for optimal monetary policy and welfare. Using wavelet-based quantile regressions, we provide a multi-layered asymmetric exposition on provincial inflation-monetary policy relationship in South Africa. We find that whiles restrictive monetary policy delivers stability in the prices of Gauteng, Mpumalanga and North West provinces, it is destabilizing for prices in Eastern Cape, KwaZulu-Natal, Limpopo, Northern Cape and Western Cape provinces. The findings are mixed, for Free State province, depending on the time horizon and quantiles. Our findings present enormous policy and welfare implications, given the inflation targeting status of South Africa and the economic disparities among the provinces of the country.
Keywords: 330; Wavelet analysis; Quantile regression; Asymmetry; Monetary policy; Provincial inflation